Numerical Study of the Effect of Winglets with Multiple Sweep Angles on Wind Turbine Blade Performance - Bayu K. Wardhana; Byeongrog Shin (Energies)
A numerical study was conducted on winglet designs with multiple sweep angles for improving the performance of horizontal axis wind turbine (HAWT) blades, and their effect on reducing the wing tip vortex was investigated by CFD analysis. The effects of sweep angles were examined through NREL Phase VI turbine blades considering a wind speed range of 7 to 25 m/s. Numerical simulations were performed using RANS equations and the SST k–ω turbulence model. The interaction of the blade rotation and wind flow was modeled using a moving reference frame method. The numerical results were found to be in good agreement with the inferences drawn from the experiments for a baseline blade without a winglet, thereby validating the computational method. The investigations revealed that multi-swept winglets predicted a 14.6% torque increment, providing higher power output than single-swept winglets compared to the baseline blade at a wind speed of 15 m/s. Implementing multiple sweep angles in winglet design can improve the blade performance effectively without further increments in winglet length.